2012
DOI: 10.4028/www.scientific.net/amm.209-211.1576
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Investigation of Public Sites in Isolated Islands within Taiwan Strait

Abstract: The selected 21 public sites for indoor air quality (IAQ) investigation located at Penghu and Kinmen Islands (Taiwan). IAQ measurements include CO2, CO, HCHO, TVOCs, bacteria, fungi, PM10, PM2.5, O3 and temperature, which were conducted during year 2010 and 2011. The results showed that the concentrations of CO, HCHO, PM10 and PM2.5 were below Taiwan EPA’s suggested IAQ threshold levels at all public sites. CO2 concentrations at hospitals and school are all exceeding category 1 threshold of 600 ppm. Besides, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Finally, 55 studies met the criteria, among which 28 were in Chinese, and 27 were in English. 25, 13 studies focused on office buildings, 34,[42][43][44]46,67,69,71,72,[74][75][76]80 26 studies were related to scho ols, 25,27,29,35,[38][39][40][41]43,[47][48][49]51,52,54,56,58,60,61,[64][65][66]68,72,73,77 and 20 studies investigated residences. 28,[30][31][32][33]36,37,45,50,53,55,…”
Section: Search Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, 55 studies met the criteria, among which 28 were in Chinese, and 27 were in English. 25, 13 studies focused on office buildings, 34,[42][43][44]46,67,69,71,72,[74][75][76]80 26 studies were related to scho ols, 25,27,29,35,[38][39][40][41]43,[47][48][49]51,52,54,56,58,60,61,[64][65][66]68,72,73,77 and 20 studies investigated residences. 28,[30][31][32][33]36,37,45,50,53,55,…”
Section: Search Findingsmentioning
confidence: 99%
“…81 More than half of these researches on schools were done on university campuses. Compared to fungi, researchers were more concerned with bacterial concentrations, with 48 studies reported bacterial concentration levels, 25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][53][54][55][56][57][58][59][60][61]63,64,[66][67][68][69][70][71][72][73][74][75][76]80 and only 29 studies reported fungal concentration levels. 25,…”
Section: Search Findingsmentioning
confidence: 99%
See 3 more Smart Citations